Peningkatan Keterampilan Perancangan Video Pembelajaran Interaktif Menggunakan Edpuzzle: Pelatihan Terhadap Guru SMP Rama Sejahtera Makassar - Zulqifli Alqadri; Banu Kisworo; Yulianti Yusal; Putri Damayanti; Sahrani U (Aktualisasi Pengabdian Masyarakat, 2025)
The community service activity aims to improve teachers skills in designing interactive learning videos using Edpuzzle as an effort to strengthen teachers digital competencies in the era of 21st century learning. The community service method used is Participation Action Research (PAR), which consists of problem identification, planning, implementation, and the stage of collecting data to evaluate the results of the activity. The training was conducted at Rama Sejahtera Junior High School, Makassar City, involving eleven teachers who were selected purposively based on their teaching experience and interest in developing digital learning media. Descriptive quantitative statistical analysis was conducted to measure the improvement in participants' abilities and their feedback on the activity. The results showed an N-Gain value of 0.501, which is in the moderate category, indicated a significant increase int teachers skills in designing interactive learning videos. The average participant feedback score reached 4.5 out of 5 (90%), with the highest aspects being the clarity of the material and the delivery of the resource persons. In addition, 82% of participants also succeeded in producing interactive Edpuzzle-based learning videos that met the eligibility criteria for use in classroom learning. These findings showed that practice-based training is effective in improving teachers technical skills and pedagogical understanding of the use of Edpuzzle as an innovative learning medium. This activity has succeeded in encouraging teachers to be more innovative in designing learning media that is more interactive and relevant to students' needs